Eccrine porocarcinoma: a case report and brief review of the literature - Rana Rafiei; Hojat Eftekhari; Arash Daryakar; Nahid Nickhah; Behnam Rafiee (Our Dermatology Online, 2016)
Eccrine Porocarcinoma is a rare, slow growing malignant tumor of eccrine sweat gland. The most common site of this tumor is lower extremity. It is characterized histologically by anaplastic cells with eccrine ductal structures which may be adjacent to a benign eccrine poroma. We present here a case of Eccrine Porocarcinoma in lower extremity, with a brief review of the literature.